Osteopontin derived from hypoxia-induced M2 macrophages promotes osteosarcoma progression through modulation of EGR3/ISG15 signaling and RIG-I expression - Chunyang Xing; Wei Hu; Liyuan Zhao (Journal of Translational Medicine)
Abstract Background Osteosarcoma (OS) is one of the most common malignancies arising in bone. Hypoxia and immune regulation are pivotal in tumor biology. However, their combined effects and mechanisms in OS remain understudied. This study aimed to explore the role and mechanism of hypoxic-induced M2 macrophages in promoting the progression of OS. Methods Differentially expressed proteins in hypoxic macrophage supernatants were detected by antibody array. Cell functional experiments, siRNA-mediated gene silencing, and overexpression transfection were used to study osteopontin (OPN) and its supernatant effect. Bioinformatics analysis was applied to investigate downstream targets and pathways, and a xenograft model was established to assess in vivo effects. Results Our data revealed that hypoxic M2 macrophage supernatant enhanced OS malignancy and epithelial-mesenchymal transition, activating cancer pathways. Hypoxia upregulated OPN in M2 macrophages, and OPN inhibition reduced its tumor-promoting effect. Early growth response 3 (EGR3) was differentially expressed in OS cells treated with the supernatant, and its overexpression inhibited OS cell migration, reversing tumor promotion. Interferon-stimulated gene 15 (ISG15), a key differentially expressed gene related to OPN and EGR3 overexpression, inhibited OS cell proliferation and migration. Additionally, OPN increased retinoic acid-inducible gene I (RIG-I) expression and enhanced signal transducer and activator of transcription 3, nuclear factor kappa B, and extracellular signal-regulated kinase signaling, while EGR3 and ISG15 overexpression inhibited these effects. Silencing ISG15 restored pathway activation and reversed the inhibitory effect of EGR3 on OS cell migration. Dual-Luciferase reporter gene assay confirmed that EGR3 activates ISG15 transcription. OPN treatment upregulated DNA (cytosine-5)-methyltransferase 1 (DNMT1) expression, and ChIP assays demonstrated that EGR3 overexpression enhanced DNMT1 binding to the EGR3 promoter. These findings suggest that OPN promotes OS malignancy by downregulating EGR3 and ISG15, and by enhancing RIG-I expression, as validated in a xenograft model of OS. Conclusion Our findings demonstrate that hypoxic-induced M2 macrophages promote OS progression through OPN-dependent mechanisms, including inhibition of EGR3 and ISG15 expression and upregulation of RIG-I. Graphical abstract